Firm Demography and Regional Development: Evidence from Italy. (15th August 2016) - Piacentino, Davide; Espa, Giuseppe; Filipponi, Danila; Giuliani, Diego
Abstract: This article contributes to the literature on firm demography and regional development in at least three different ways. First, consumption, rather than employment, which is the most common variable seen in literature, is used to measure the impact of firm demography on regional development. Second, while the literature is mainly focused on the relationship between new business formation and regional development, we investigate both entry and exit flows of firms. Third, we decompose each of these flows into spatial and sectoral components. The empirical investigation looks at the Italian regions with reference to the period 2004–2009. Results seem to be substantially divergent between the South and the rest of Italy.